2021
DOI: 10.1111/jocd.13931
|View full text |Cite
|
Sign up to set email alerts
|

Increases in uric acid and monocyte‐high‐density lipoprotein ratio as possible atherosclerotic indicators in acne patients using isotretinoin

Abstract: Purpose We aimed to reveal the relationship of serum uric acid (SUA) with monocyte‐high‐density lipoprotein ratio (MHR) and other inflammatory markers in acne patients before and after isotretinoin treatment. In this way, we can try to shed light on the relationship between isotretinoin treatment and atherosclerosis. Methods Two hundred twenty‐four acne patients who administered isotretinoin (0.5‐1 mg/kg/day) were enrolled in the study. In the pretreatment phase and 3 months after treatment, MHR, SUA, mean pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…Systemic inflammation triggers lymphopenia, causing an increase in NLR levels (19). In the current study, decreased NLR levels response to the treatment were in line with previous studies (15,16,20). Previous studies have demonstrated different results on platelet values (21,22).…”
Section: Discussionsupporting
confidence: 91%
“…Systemic inflammation triggers lymphopenia, causing an increase in NLR levels (19). In the current study, decreased NLR levels response to the treatment were in line with previous studies (15,16,20). Previous studies have demonstrated different results on platelet values (21,22).…”
Section: Discussionsupporting
confidence: 91%
“…Studies in recent years have generally focused on the effects of isotretinoin on inflammatory markers such as NLR and monocyte/high-density lipoprotein ratio in patients with moderate to severe acne. 13,23 Acne severity is categorized as mild, moderate, or severe according to the extent and types of lesions, and often the clinician's experience. In this study, we used CASS and PASS, which were determined according to the physician's opinion and the patient's self-perception, respectively, as well as GAGS for objective evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…SII has never been investigated before in acne, where we draw attention to the importance of the inflammatory response in its pathogenesis. Studies in recent years have generally focused on the effects of isotretinoin on inflammatory markers such as NLR and monocyte/high‐density lipoprotein ratio in patients with moderate to severe acne 13,23 . Acne severity is categorized as mild, moderate, or severe according to the extent and types of lesions, and often the clinician's experience.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that there is a relationship between coronary artery plaque load and HDL-C [6]. Various studies conducted on this topic have found a relationship between uric acid to HDL-C (UHR) and metabolic syndrome and atherosclerotic diseases [7,8].…”
Section: Early Onlinementioning
confidence: 99%